Synthesis of novel three-dimensional mesoporous nitrogen doped graphene supported Pt nanoparticles as superior catalyst for hydrogen generation. (18th October 2018) - Ma, Tianjiao; Zhang, Mingmei; Liu, Hong; Wang, Ying; Pan, Denghui
Abstract: In this work, three dimensional mesoporous nitrogen doped graphene (3DMNG) is fabricated by hydrothermal method and assists by tube furnace calcination. The experimentally obtained 3DMNG has a porous structure (pore size at 0–55 nm) and a large specific surface area (about 1050 m 2 /g). The electrochemical results demonstrate that the electrochemical active surface area (ECSA) of 3DMNG is about 24.34 m 2 /g, the initial overpotential was 70 mV, the Tafel slope was 103.91 mV/dec, and the impedance is about 2.8Ω, which is more prominent than that of other similar carbon materials. Moreover, 3DMNG plays an important role in uniforming Pt nanoparticles (1.5 nm) using microwave synthesis method. The electrochemical results testify that the ECSA of Pt/3DMNG is about 179.70 m 2 /g, the initial overpotential is close to 0 mV, the Tafel slope is only 30.72 mV/dec, and the impedance is 2.2Ω, which is a significant improvement compared with 3DMNG. The superior electrocatalytic hydrogen evolution performance of Pt/3DMNG is attributed to the synergistic coupling effect between the 3DMNG and Pt nanoparticles. Highlights: A novel three dimensional mesoporous nitrogen doped graphene were designed. 3DMNG plays an important role in uniforming Pt quantum dots (1.5 nm) using microwave synthesis method. Mesoporous structure is successfully formed using KOH as the pore forming agent. Pt/3DMNG demonstrates superior electrocatalytic hydrogen evolution performance.